Treatment efficiency of effluent prawn culture by wetland with floating aquatic macrophytes arranged in series - Henares, M. N. P. [UNESP]; Camargo, A. F. M. [UNESP] (Int Inst Ecology, 2014)
The efficiency of a series of wetland colonized with Eichhornia crassipes and Salvinia molesta to treat the effluent of a giant river prawn (Macrobrachium rosenbergii) broodstock pond was evaluated in this study. The experimental design was completely randomized and was performed in 9 rectangular tanks (1.6 m(3)) with three treatments (constructed wetlands) and three replicates. The treatment types included: a wetland colonized with E. crassipes and S. molesta (EcSm) arranged sequentially, a wetland with E. crassipes only (Ec) and a wetland with S. molesta only (Sm). The means of suspended particulate material (SPM), total inorganic nitrogen (TIN), total Kjeldahl nitrogen (TKN), P-orthophosphate (PO4-P) and total phosphorus (TP) of the treated effluents were compared using ANOVA followed by Tukey's test (P < 0.05). The effluent treated in Ec and EcSm wetlands exhibited lower SPM concentrations. The Ec wetland reduced TIN, TKN, PO4-P and TP by 46.0, 43.7, 44.4 and 43.6%, respectively. In the EcSm wetland, the reduction of TIN (23.0%), TKN (33.7%) and PO4-P (26.7%) was similar to the Sm wetland (19.8% TIN, 30.9% TKN and 23.8% PO4-P). The Ec wetland was more efficient in treating pond effluent due likely to the higher root surface of E. crassipes, which forms an extensive area favorable to retention and adsorption of debris and absorption of nutrients.

Neste estudo foi avaliada a eficiência de uma wetland povoada com Eichhornia crassipes e Salvinia molesta para o tratamento do efluente de um viveiro de manutenção de reprodutores do camarão-da-malásia (Macrobrachium rosenbergii). Um experimento totalmente casualizado foi realizado em 9 tanques retangulares (1,6 m3 ) com 3 tratamentos (wetlands construídas) e 3 repetições. Os tratamentos foram: wetland povoada com E. crassipes e S. molesta (EcSm) dispostas nesta sequência, wetland somente com E. crassipes (Ec) e wetland somente com S. molesta (Sm). Os valores de material particulado em suspensão (MPS), nitrogênio inorgânico total (NIT), nitrogênio Kjeldahl total (NKT), P-ortofosfato (P-PO4 ) e fósforo total (PT) dos efluentes tratados foram comparados pela ANOVA seguida do teste de Tukey (P<0,05). A wetland Ec reduziu a concentração de NIT, NKT, P-PO4 e PT em 46,0%, 43,7%, 44,4% e 43,6%. Na wetland EcSm a redução de NIT (23,0%), NKT (33,7%) e P-PO4 (26,7%) foi semelhante à observada na wetland Sm (19,8% para NIT, 30,9% para NKT e 23,8% para P-PO4 ). A wetland povoada com E. crassipes é mais eficiente no tratamento do efluente do viveiro, provavelmente devido a maior superfície radicular da macrófita que permite a formação de uma extensa área propícia à retenção e adsorção dos detritos e à absorção dos nutrientes.
Eficiência de wetland com macrófitas aquáticas flutuantes dispostas em serie para o tratamento do efluente do cultivo de camarão
Keywords: Constructed wetland; Eichhornia crassipes; Macrobrachium rosenbergii; Salvinia molesta; Wetland construída; Eichhornia crassipes; Macrobrachium rosenbergii; Salvinia molesta.